EXPERIMENTAL STUDY ON IN-POND HEAT EXCHANGER PROVIDED WITH TWISTED TAPES - K, Karunamurthy; Singh, Nayan; Singh, Vivek (Asian Journal of Pharmaceutical and Clinical Research, 2017)
In-pond heat exchangers (IHE) are used in salinity gradient solar ponds (SGSP), to transfer heat from hot saline water of the lower convective zone to the heat transfer medium. The performance of the SGSP depends on the performance of the IHE, which in turn depends on the method of heat transfer augmentation. A laboratory model IHE was fabricated to augment the heat transfer using helical twisted tapes (HTTs). The effects of varying twist ratio and double TTs on pressure drop and heat transfer were studied in this experimental work. Conventional HTTs of three twist ratios (Y=7, 9, 11), twin TTs of co-swirl flow (CoTT), and counter-swirl TTs (CTT) with Y=7 were provided in the flow path of the heat exchanger tube for analysis. From the results, it is observed that TTs with less twist ratio yielded higher rate of heat transfer by sacrificing the pressure drop. Compared to single TT, double TT provided better thermal performance. The pressure drop and rate of heat transfer for CTT are more compared to all other cases, including double TT with co-swirl flow.